2009
DOI: 10.1021/ja806688s
|View full text |Cite
|
Sign up to set email alerts
|

Process of Accumulation of Metal Ions on the Interior Surface of apo-Ferritin: Crystal Structures of a Series of apo-Ferritins Containing Variable Quantities of Pd(II) Ions

Abstract: Accumulation of metal ions on protein surfaces is an important subject in the field of materials science because these processes are applicable to the preparation of bioinspired inorganic materials. While previous studies related to this subject have focused on the preparation of nanomaterials using protein scaffolds, the detailed processes of metal ion deposition and metal core formation on a protein surface require clarification. Elucidation of the coordination structures of multinuclear metal binding sites … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
101
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 93 publications
(106 citation statements)
references
References 51 publications
5
101
0
Order By: Relevance
“…The cage can accommodate a number of other metal ions/ complexes or small organic molecules [19][20][21]. The pHdependent assembly/disassembly properties are advantageous with respect to encapsulation of larger metal complexes, organic molecules or nanoparticles [22,23].…”
Section: Ferritinmentioning
confidence: 99%
“…The cage can accommodate a number of other metal ions/ complexes or small organic molecules [19][20][21]. The pHdependent assembly/disassembly properties are advantageous with respect to encapsulation of larger metal complexes, organic molecules or nanoparticles [22,23].…”
Section: Ferritinmentioning
confidence: 99%
“…It is important to notice that most of the mineralization reactions that have been successfully carried out are not specific to iron, suggesting that the electrostatic character of the interior surface of the protein cage is the major player in the mineralization process. Besides the presence of an electrostatic gradient that favours the concentration of cations inside the cavity, it is of great value to have multiple metal binding/nucleation sites able to incorporate efficiently the required metal, which are likely to act as starting points and metal particle seeds for the mineralization reaction Ueno et al, 2009). Other parameters have to be taken into account for the preparation of protein-enclosed nanomaterials of biotechnological value, such as: the specific ferritin molecule to be used as a template; the oxidant/reducing agent; and the reaction conditions (i.e., ionic strength, pH, temperature, presence of chelating molecules, etc.).…”
Section: Biomimetic Synthesis Of Nanoparticles In Ferritins and Dpsmentioning
confidence: 99%
“…These Asp and His functional groups can be bound to Pd II ions with cooperative disruption of the hydrogen bonds and alterations of the conformation of coordinated amino acids in a manner similar to that which occurs at Site B of Rh·HEWL (Figure 4 a). [23] Therefore, it is suggested that these metal clusters in native proteins are formed by accumulation of aqua metal complexes. The reactions are coupled with the rearrangement of hydrogen bonds and conformational changes of amino acid residues, as observed in our model systems.…”
Section: Accumulation Mechanism Of Rhmentioning
confidence: 99%
“…The results indicate that the number of Pd II ions accumulated by apo-Fr increases when different coordination structures are adopted at the specific binding sites on the interior surface of apo-Fr. [23] However, there is only limited information about the cooperative roles of hydrogen bonds and amino-acid residues in the accumulation reactions, because the crystal structure with a high content of Pd II ions was obtained at low resolution. [23,30] If we can construct appropriate metal ion/protein surface models, we expect to gain an in-depth understanding of the accumulation mechanism.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation